Analysis of Rice-Business Insurance Program (Autp) In Ponorogo District (Case Study In Agriculture And Fisheries Department of Ponorogo District Work Program 2018-2019) - Samidi; Ahsin Daroini; Abu Talhah (Faculty of Agriculture, Merdeka University Surabaya, 2019)
This research aimed: (a) to analyze the implementation of rice farm business insurance (AUTP) in the Ponorogo District Work Area; (b) to find out the factors that influence the implementation of the AUTP program in Ponorogo district; (c) to prove that the agricultural sector in Ponorogo district is a base and superior sector. This research uses a qualitative approach, where the reality under study is understood by a holistic approach and does not take measurements on certain parts of the reality. This study uses Internal Factor Analysis, External Factor Analysis, Klassen Typology and LQ (Location Quetiont) Analysis. The results of the research show that: (a) Implementation of AUTP in Ponorogo district cannot be said be maximal. This is reinforced by the results of the typology Klassen analysis in Ponorogo district in the